Remembering the nation, disremembering women? : stories of the South African transition - Samuelson, M A (Department of English Language and Literature, 2016)
The thesis explores the making of nationhood, and its contestation, in narrative representations of women during the South African transition. This temporal span extends across the first decade of democracy and the first two terms of governance following the historic 1994 elections. The transition is a fertile temporal zone in which new myths and symbols are generated. My interest lies in the new national symbols and myths that emerge from this historical moment and the ways in which they have been figured through images and appropriations of women and their bodies. Women's bodies, I argue, are the contested sites upon which nationalism erects its ideological edifices. I engage with the mutually informing productions and performances of gender and nation, and the re-membering of a previously divided and divisive South Africa as a unified 'rainbow' nation. I proceed by tracing narrative acts of memory and repression, with a specific focus on the re-memberings and dismemberings of women's bodies as they are reconstituted as ideal vessels for a national allegory. Includes bibliographical references (pages 211-238).